2022
DOI: 10.4196/kjpp.2022.26.2.69
|View full text |Cite
|
Sign up to set email alerts
|

Altered synaptic connections and inhibitory network of the primary somatosensory cortex in chronic pain

Abstract: Chronic pain is induced by tissue or nerve damage and is accompanied by pain hypersensitivity (i.e., allodynia and hyperalgesia). Previous studies using in vivo two-photon microscopy have shown functional and structural changes in the primary somatosensory (S1) cortex at the cellular and synaptic levels in inflammatory and neuropathic chronic pain. Furthermore, alterations in local cortical circuits were revealed during the development of chronic pain. In this review, we summarize recent findings regarding fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…The posterior central gyrus is also known as the primary sensory cortex (S1). Both human and animal experiments have shown that maladaptive changes in S1 are a characteristic feature of neuropathic pain [32,33] . Studies have demonstrated that changes occur in the structure and function of S1 in patients with phantom limb pain (PLP) [34] Complex regional pain syndrome (CRPS) [35] and spinal cord injury (SCI) [36] .…”
Section: Discussionmentioning
confidence: 99%
“…The posterior central gyrus is also known as the primary sensory cortex (S1). Both human and animal experiments have shown that maladaptive changes in S1 are a characteristic feature of neuropathic pain [32,33] . Studies have demonstrated that changes occur in the structure and function of S1 in patients with phantom limb pain (PLP) [34] Complex regional pain syndrome (CRPS) [35] and spinal cord injury (SCI) [36] .…”
Section: Discussionmentioning
confidence: 99%
“…The S1 is a brain region critical in the processing of pain signaling that has been reported to show functional or structural changes in chronic pain conditions [ 43 ]. The S1 of chronic pain patients was actively displayed by fMRI [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the predominant somatosensory cortex projections to the Gr originate from S1-HL, aligning anatomically with somatotopically organized ascending input. Projections from the primary somatosensory cortex, which exhibits hyperexcitability and neuroplasticity during chronic pain [71][72][73] , may represent a relevant source for descending modulation of Gr activity during neuropathic pain.…”
Section: Gr Vpl-pns and Inhibitory Neurons Are Differentially Innerva...mentioning
confidence: 99%